Real world evidence study on treatment patterns and health resource utilization in patients with HR+/HER2- locally advanced or metastatic breast cancer in Korea. (31st December 2022) - Novick, Diego; Lee, Sae Young; Koo, Dong Hyun; Szende, Agota; Colman, Sam
Abstract: Objective: To understand current treatment patterns and health care resource utilization (HRU) of women with locally advanced or metastatic breast cancer (advanced breast cancer; ABC) in Korea overall and within patients who had progressed with prior endocrine therapy (as first-line treatment for metastatic disease) and patients with no prior systemic treatment (for advanced disease). Methods: A chart review was conducted in 109 patients (women ≥ 18 years old with HR+/HER2- ABC diagnosed between 2015 and 2017) from 11 hospitals. Anonymized data on patient characteristics, treatment patterns and HRU was abstracted. Results: Mean (range) age of all patients was 57.5 (40–81) years. Overall, the most common first-, second- and third-line systemic therapy after diagnosis of ABC were letrozole ± palbociclib (51%), endocrine therapy (ET)±everolimus (42%) or chemotherapy (ChT) (39%), and ChT (68%), respectively. In patients progressed with ET ( n = 33) and those with no prior systemic treatment ( n = 52), the most common first-line treatments were letrozole (82%) and letrozole + palbociclib (42%), respectively. The percentage of patients with at least one grade 3 or higher adverse event during first-line therapy was 93.1% vs 39.2% in patients on a ChT based regimen ( N = 29) vs. ET ( N = 74). Overall, oncologist visits, at an annual rate of 9.27 (95% CI: 8.87, 9.69) visits per month, and hospitalizations, with an annual rate of 0.44 (95% CI: 0.36, 0.54), and mean (SD) length of stay of 14.3 (10.32) days, were the key drivers of HRU. Conclusions: These findings on real world HRU reflected clinical guidelines and severity of ABC. Results can inform future evaluations of new ABC treatments that estimate the health economic impact of their adoption in Korea.